Peningkatan Prestasi Belajar Prakarya pada Materi Pokok Pengolahan Bahan Pangan Buah Menjadi Makanan Melalui Pendekatan Quantum Teaching - Anawati Hidayah (Academy of Education Journal, 2018)
Learning methods cannot always be used in every learning. A teacher must be able to provide interesting and fun lessons. Many methods and media that discuss about us that can be used in teaching and learning activities. The aim is to provide experience to students. Because professional teacher educators are required to prefer to use and use appropriate methods so that students can be interested and learn the results of learning in accordance with the learning objectives. The purpose of this Classroom Action Research is to discuss Quantum Learning to improve the learning achievements of the Workshop on Fruit Food for Food in class VII A of SMP Negeri 1 Nusawungu in the 2016/2017 Academic Year. Quantum Teaching in Subjects Teaching material Teaching Food Materials Into Food in class VII A SMP Negeri 1 Nusawungu in the 2016/2017 Academic Year is that discussing Quantum Teaching can improve learning in class VII A SMP Negeri 1 Nusawungu. Student learning achievement increases with the results of daily tests at each stage. The completeness rate in the initial study was 47%, cycle I 71%, and cycle II 88%. The average results of daily tests also increased by 65 in the initial study, 77 in the first cycle and 86 in the second cycle. Increase the average increase in total learning outcomes from the initial conditions to the second cycle 21.